ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS USED TRADITIONALLY FOR THE MANAGEMENT OF VARIOUS AILMENTS IN KAURA NAMODA, ZAMFARA STATE, NIGERIA - Tukur, Khalid; Musawa, Bello Bello; Abubakar, Mukhtar Lawal; Muhammad, Mustapha Sani; Abba, Hammanjoda Salihu (FUDMA JOURNAL OF SCIENCES, 2024)
The research was carried out between December 2022 and March 2023. Eighty-eight (88) informants provided information on traditional knowledge via a semi-structured questionnaire. The demographic data of the respondents was presented using descriptive statistics. The popularity of the referenced species was examined using Use Consensus Values (UCs) and Relative Frequency of Citation (RFC). There were 88 informants, of which 27% were women and 73% were men. Most respondents (35 percent) are between the ages of 51 and 60. Just 6.8% of the respondents were single, while the majority, 80.7%, were married of the responders, and 64.8% had never attended college. Herbalists made up 42 percent of the respondents. A total of twenty-four (24) families’ worth of plant species were collected. The dominant family is called Fabaceae with eighteen (18) members, and malvaceae, with three (3) and four (4) members, in order of precedence. There was one (1) member in each of the following families: SolanaceaeAsteraceae, Asclepiadaceae, Zingiberaceae, Curcubitaceae, Convulvolaceae, Amaryllidaceae, Apocynaceae, Ebanaceae, Rutaceae, Moringaceae, Rubiaceae, Zygophylaceae, and Annonaceae The plant Azadirachta indica exhibited the greatest Use Concensus Value (UC) of 0.40 and Relative Frequency of Citation (RFC) of 0.20. Most plants are used to treat a variety of conditions, including piles, diabetes etc., asthma, malaria, typhoid, stomachaches, anti-snake bites, diarrhea, yellow fever, whereas certain herbs arouse libidinal urges.